Development of a flow standard to enable highly reproducible measurements of deformability of stored red blood cells in a microfluidic device. Issue 5 (1st April 2020) - Robidoux, Jonathan; Laforce‐Lavoie, Audrey; Charette, Steve J.; Shevkoplyas, Sergey S.; Yoshida, Tatsuro; Lewin, Antoine; Brouard, Danny
Abstract : BACKGROUND: Great deformability allows red blood cells (RBCs) to flow through narrow capillaries in tissues. A number of microfluidic devices with capillary‐like microchannels have been developed to monitor storage‐related impairment of RBC deformability during blood banking operations. This proof‐of‐concept study describes a new method to standardize and improve reproducibility of the RBC deformability measurements using one of these devices. STUDY DESIGN AND METHODS: The rate of RBC flow through the microfluidic capillary network of the microvascular analyzer (MVA) device made of polydimethylsiloxane was measured to assess RBC deformability. A suspension of microbeads in a solution of glycerol in phosphate‐buffered saline was developed to be used as an internal flow rate reference alongside RBC samples in the same device. RBC deformability and other in vitro quality markers were assessed weekly in six leukoreduced RBC concentrates (RCCs) dispersed in saline‐adenine‐glucose‐mannitol additive solution and stored over 42 days at 4°C. RESULTS: The use of flow reference reduced device‐to‐device measurement variability from 10% to 2%. Repeated‐measure analysis using the generalized estimating equation (GEE) method showed a significant monotonic decrease in relative RBC flow rate with storage from Week 0. By the end of storage, relative RBC flow rate decreased by 22 ± 6% on average. CONCLUSIONS: The suspension of microbeads was successfully used as a flow reference to increase reproducibility of RBC deformability measurements using the MVA. Deformability results suggest an early and late aging phase for stored RCCs, with significant decreases between successive weeks suggesting a highly sensitive measurement method.